Enhancing contraceptive choice for postpartum women in sub-Saharan Africa with the progesterone vaginal ring: a review of the evidence - RamaRao S; Ishaku S; Liambila W; Mane B (Dove Medical Press, 2015)
Saumya RamaRao,1 Salisu Ishaku,2 Wilson Liambila,3 Babacar Mane41Population Council, Reproductive Health Program, New York, NY, USA; 2Population Council, Reproductive Health Program, Abuja, Nigeria; 3Population Council, Reproductive Health Program, Nairobi, Kenya; 4Population Council, Reproductive Health Program, Dakar, SenegalAbstract: It is increasingly recognized that women who have just given birth have a high unmet need and require contraceptive protection in the first year postpartum. A majority of women in developing countries do breastfeed exclusively but for short durations, hence they may be sometimes unknowingly exposed to the risk of pregnancy if they are relying on nursing for contraceptive protection. The WHO’s Medical Eligibility Criteria for Contraceptive Use recommends the use of different contraceptives in the first year postpartum depending on whether the woman is nursing or not and the time since delivery. Some of the options available for breastfeeding women include implants, IUDs and injectables, which can be obtained only from a trained family planning provider. Since 2013, Population Council has been carrying out a study in Senegal, Nigeria, and Kenya to assess the acceptability of progesterone vaginal ring (PVR) as a new contraceptive option designed specifically for use by breastfeeding women to extend the period of lactational amenorrhea and promote birth spacing. Breastfeeding in sub-Saharan Africa is near universal with fairly long durations, a situation that increases the effectiveness of PVR. Each ring delivers a daily dose of 10 mg of progesterone and can be used continuously up to 3 months with a woman being able to continue with its use up to 1 year (four rings used consecutively). Preliminary results indicate that many women who had used the method found it acceptable and their partners supported its use. Activities aimed at having PVR registered and made available in focal countries are ongoing. Integration of family planning and immunization services for mothers and their newborns will be a key strategy in introducing PVR into targeted health care markets. Given that the use of PVR does not require extensive clinical training, it will be easier to integrate it at all levels of the health system from tertiary health facilities to community-based services. The PVR has been recently included in the WHO Model List of Essential Medicines and the WHO’s fifth edition of the Medical Eligibility Criteria for Contraceptive Use which should facilitate its introduction into the public and private sectors.Keywords: breastfeeding, nursing, lactational amenorrhea, postpartum family planning, sub-Saharan Africa, contraception